2022
DOI: 10.1111/pbr.13020
|View full text |Cite
|
Sign up to set email alerts
|

Fine mappingPsPS1, a gene controlling pod softness that defines market type in pea (Pisum sativum)

Abstract: Pea is an important grain and vegetable crop with a large genome of $4.45 Gb. The softness of pod is key to the quality of pea, yet the genes controlling softness remain unknown. Here, the pod softness phenotype was visually scored at the fully mature stage, which suggested that this trait was a composite trait governed by two genes.Bulked segregant analysis sequencing (BSA-Seq) using the soft-and hard-podded pools from the F 2 detected a strong peak of Δ (SNP-index) on chromosome 1 and a weaker peak on chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Subsequent fine-mapping led to the delineation of a 1.33Mb interval (Chr4 18.18-19.51Mb, ZW6) (Extended Data Fig. 8a-e, and Supplementary [25][26]. We found that all the accessions with fasciated phenotypes were clustered together within haplotype 5 of this 1.33Mb interval (Extended Data Fig.…”
Section: Fasciationmentioning
confidence: 75%
See 1 more Smart Citation
“…Subsequent fine-mapping led to the delineation of a 1.33Mb interval (Chr4 18.18-19.51Mb, ZW6) (Extended Data Fig. 8a-e, and Supplementary [25][26]. We found that all the accessions with fasciated phenotypes were clustered together within haplotype 5 of this 1.33Mb interval (Extended Data Fig.…”
Section: Fasciationmentioning
confidence: 75%
“…24 and Supplementary Table 32) and differential gene expression analysis, we identified Psat02G0011300 as a gene candidate for PsOs1 (Supplementary Figs. [25][26], which encodes a SIAMESE-related protein (SIM/SMR), a cyclin-dependent protein kinase inhibitor (CKI), influencing cell division and enlargement during the cell cycle and consequently altering plant cell size 75 . Functional validation from the VIGS (Supplementary Fig.…”
Section: A Quantitative Trait Essential In Pea Breedingmentioning
confidence: 99%
“…Subsequent fine-mapping led to the delineation of a 1.33Mb interval (Chr4 18.18-19.51Mb, ZW6) (Extended Data Fig. 8a-e, and Supplementary Table [17][18][19][25][26]. We found that all the accessions with fasciated phenotypes were clustered together within haplotype 5 of this 1.33Mb interval (Extended Data Fig.…”
Section: Fasciationmentioning
confidence: 78%
“…and differential gene expression analysis, we identified Psat02G0011300 as a gene candidate for PsOs1 (Supplementary Figs. [25][26], which encodes a SIAMESE-related protein (SIM/SMR), a cyclin-dependent protein kinase inhibitor (CKI), influencing cell division and enlargement during the cell cycle and consequently altering plant cell size 75 . Functional validation from the VIGS (Supplementary Fig.…”
Section: A Quantitative Trait Essential In Pea Breedingmentioning
confidence: 99%
“…The peas have a notably low reproductive coe cient, as compared to the food crops, such as wheat and rice (Li et For BSA-seq, it is not necessary for large segregating populations to map target genes, and it has been successfully employed in peas to identify candidate regions and develop linked molecular markers for various traits, including leaf shape (Zheng et al 2018), pod softness (Zhang et al 2022b), and disease resistance (Fondevilla et al 2022;Wu et al 2022). In this study, a 10.4 Mb candidate region in chr6LG2 associated with the FwS1 was pinpointed using the BSA-seq method.…”
Section: Discussionmentioning
confidence: 99%